The synthesis and evaluation of BIS-1,2,3- triazolylidene(carbazolide) gold complexes as anticancer agents - Van der Westhuizen, Danielle (My University, 2021)
Gold pincer complexes were evaluated for their potential as suitable anticancer agents. The use of a multidentate pincer ligand composed of an anionic carbazolide backbone and two flanking 1,2,3 triazol 5 ylidenes trz was proposed for the effective redox stabilization of the gold III complex under physiological conditions.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2021
Keywords: Ligands (Biochemistry); Antineoplastic agents